2013
DOI: 10.1093/gji/ggs104
|View full text |Cite
|
Sign up to set email alerts
|

A new Late Cretaceous to Present APWP for Asia and its implications for paleomagnetic shallow inclinations in Central Asia and Cenozoic Eurasian plate deformation

Abstract: Based on a compilation of 533 Cretaceous to present-day paleomagnetic poles obtained from both sedimentary and igneous rocks, we present a new analysis of the so-called "Asian inclination anomaly" and demonstrated the anomaly to be twofold: a 2 nd -order anomaly, characterized by high paleolatitudes in Indochina and low paleolatitudes over Tibet and Central Asia, is superimposed on a 1 st -order anomaly, characterized by Cenozoic low paleolatitudes found all over north-eastern Asian stable blocks. The analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
1
3

Year Published

2014
2014
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 118 publications
(271 reference statements)
3
107
1
3
Order By: Relevance
“…For example, systematically shallow inclinations have led to questioning of the GAD hypothesis and invocation of persistent ancient non-axial dipole field geometries (e.g., Chauvin et al, 1996;van der Voo and Torsvik, 2001). In tectonic studies, shallow inclinations have been suggested to indicate major paleolatitude differences between the past and present, which implies significant poleward tectonic transport (Kent and Irving, 2010;Tan et al, 2010;Lippert et al, 2011;Cogné et al, 2013;Muttoni et al, 2013). These issues make it important to have methods to detect and correct for inclination shallowing.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For example, systematically shallow inclinations have led to questioning of the GAD hypothesis and invocation of persistent ancient non-axial dipole field geometries (e.g., Chauvin et al, 1996;van der Voo and Torsvik, 2001). In tectonic studies, shallow inclinations have been suggested to indicate major paleolatitude differences between the past and present, which implies significant poleward tectonic transport (Kent and Irving, 2010;Tan et al, 2010;Lippert et al, 2011;Cogné et al, 2013;Muttoni et al, 2013). These issues make it important to have methods to detect and correct for inclination shallowing.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, recent geological studies show that the Eurasian plate was probably not a rigid plate during the Cenozoic, and relative tectonic movements may still have occurred between the European and the Siberian blocks. Thus the use of European poles would induce a greater intracontinental shortening estimate in Asia when paleomagnetic data are compared (Yegorova and Starostenko, 1999;Trifonov, 2004;Dupont-Nivet et al, 2010a, b;Cogné et al, 2013). Cogné et al (2013) constructed a new APWP for Eastern Asia using the paleomagnetic data obtained from the Siberian Craton, Amuria, the Korean Peninsula and the North and South China blocks.…”
Section: Cretaceous Paleopoles Of the Mangkang Areamentioning
confidence: 99%
“…Boa parte desses persistiu, em pulsos descontínuos, desde o Cretáceo até o Neógeno. A correlação desses processos com a origem e evolução do Sistema de Riftes Cenozoicos do Sudeste do Brasil atualmente é aceita com certo consenso entre os pesquisadores do tema (Almeida & Carneiro, 1998;Riccomini, 1989;Riccomini et al 2004;Zalán & Oliveira, 2005;Cogné et al, 2011Cogné et al, , 2013Zalán, 2012), entretanto o mesmo não ocorre com relação aos mecanismos formadores e modificadores destas feições geomorfo-estruturais.…”
Section: Origem E Evolução Tectônicaunclassified
“…A sedimentação foi essencialmente continental, o que resultou em pacote sedimentar com espessura máxima de 800-850 m no depocentro, próximo à porção centronordeste da bacia (Riccomini, 1989;Marques, 1990;Riccomini, et al, 2004;Carvalho, et al, 2011;Cogné, et al, 2013). Em sua porção sudoeste, atravessada pelo perfil sísmico, o pacote sedimentar não ultrapassa 200 m de espessura (Carvalho, et al, 2011).…”
Section: Graben De Taubatéunclassified
See 1 more Smart Citation